Psychological Dynamics of Social Interaction in Face-to-Face and Digital Communication - Hagen, Sogeri; Burat, Afu; Kahale, Heremana (Journal Social Civilecial, 2024)
The present work addresses the areas of interest of psychology that concern social interactions and the roles of cognitive processes, affective states, nonverbal behaviors, and cultural values in interactions. Interaction affects human aspects such as the relationship between two persons or entities, and organization of societies. The distinct notion of this research topic is based on modern people’s understanding of how digital communication stands in relation to face-to-face communication in present society. The study employs qualitative interviews and observations of people and communities to examine the roles of empathy, fear or distrust to interpersonal and social cognition. Further, it looks at the part played by perception and attribution in determining behavior and the judgments people make about others, in different settings. Conflict recognition and escalation are also extensively covered in this paper as well as possible body language, facial expressions, and tone of voices as lenses of meaning-making in social interactions. In addition, culture and social relations are taken into account when defining how various environments define interaction between people. The survey results add to the existing body of knowledge regarding social behavior of man especially given the advent of social media. This study thus fills the research gaps of investigating the methods through which digital interaction affects human relations, in light of the reviewed research findings above. This work shows that social behavior is a complex domain of study, and that understanding human action means not only considering how people relate to one another, but also how their brains process information about the social world.